Investigating the Impact of COVID-19 toward Depression Rate of Indonesian Senior High Schools Teachers - Malini, Helma (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
The COVID -19 pandemic, which has been ongoing for over a year, has become a burden to the world, causing anxiety and depression. The purpose of this study is to investigate the depression and stress levels of senior high school teachers in Indonesia during the COVID-19 outbreak since they have experienced substantial teaching situations change as a result of it. In particular, the changes in their professional, as well as personal lives, pose challenges during the pandemic. This quantitative study distributing questionnaires to 50 high school teachers in Indonesia. The findings indicate that social support is the most significant factor (0,46%) needed to prevent depression and stress among the teachers. Meanwhile, workload and role conflict cover 0,74% and 0,84% respectively of variables that teachers can change with the assumption that both variables exist even before a pandemic arises. This study also reveals that teachers continue to receive less attention and support, especially in terms of their stress and depression coverage. It is because the prevailing perception is that teachers should be the ones giving attention, not the ones receiving it. The study is that to withstand the Pandemic's uncertainty where high school teacher able to minimize and overcome their depressions.